2007
DOI: 10.1561/101.00000006
|View full text |Cite
|
Sign up to set email alerts
|

Economics of Forest Ecosystem Carbon Sinks: A Review

Abstract: Carbon terrestrial sinks are seen as a low-cost alternative to fuel switching and reduced fossil fuel use for lowering atmospheric CO 2 . In this study, we review issues related to the use of terrestrial forestry activities to create CO 2 offset credits. To gain a deeper understanding of the confusing empirical studies of forest projects to create carbon credits under Kyoto, we employ meta-regression analysis to analyze conditions under which forest activities generate CO 2 -emission reduction offsets at compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 45 publications
2
44
1
Order By: Relevance
“…For example, Richards et al (1993) found that increasing the discount rate from 3 to 7 percent doubled the marginal cost of sequestration. However, van Kooten and Sohngen (2007) found that the discount rate had no statistically significant influence on financial costs in their meta-analysis of 68 forest offset cost studies. They attribute this to the fact that most of the financial costs occur in the earliest years of forestry projects, reducing the importance of discounting.…”
Section: Opportunity Cost Of Land and Discount Ratesmentioning
confidence: 97%
“…For example, Richards et al (1993) found that increasing the discount rate from 3 to 7 percent doubled the marginal cost of sequestration. However, van Kooten and Sohngen (2007) found that the discount rate had no statistically significant influence on financial costs in their meta-analysis of 68 forest offset cost studies. They attribute this to the fact that most of the financial costs occur in the earliest years of forestry projects, reducing the importance of discounting.…”
Section: Opportunity Cost Of Land and Discount Ratesmentioning
confidence: 97%
“…Their results show that the optimal number of trees in the stand increases with carbon price. In addition, they find carbon storage costs to be low in comparison with figures presented in earlier meta-analyses (Richards and Stokes 2004;van Kooten and Sohngen 2007). The study of Zhou (2001) analyzes the optimal stand management of Scots pine in Sweden, fixing the number of thinnings to one, but optimizing the initial density.…”
Section: Economic Optimization Of Carbon Storage In Forest Standsmentioning
confidence: 99%
“…Landowners can influence the stock of carbon that is sequestered over time through management and harvesting plans, while more extensive changes in land use types (land conversion) carry permanent changes in potential carbon stocks [118][119][120]. Carbon sequestration is an example of point source positive externality and potentially amenable to incentive-based policy approaches like the ones we have been discussing.…”
Section: Forest Carbonmentioning
confidence: 99%